Equinodermos del Museo de Zoología de la Universidad de Costa Rica - Alvarado, Juan José; Chacón-Monge, José Leonardo; Solís-Marín, Francisco Alonso; Pineda-Enríquez, Tania; Caballero-Ochoa, Andrea Alejandra; Solano Rivera, Sofía; Romero Chaves, Raquel (Revista de Biología Tropical, 2017)
Echinoderms from the Museum of Zoology from the Universidad de Costa Rica. The Museum of Zoology, Universidad de Costa Rica (MZUCR) was founded in 1966 and houses the most complete collection of vertebrates and invertebrates in Costa Rica. The MZUCR currently has 24 collections containing more than five million specimens, and more than 13 000 species. The earliest collections date back to 1960 and include fishes, reptiles, amphibians, polychaetes, crustaceans and echinoderms. For the latter group, the MZUCR has a total of 157 species, in 1 173 lots and 4 316 specimens. These 157 species represent 54% of the total species of echinoderms from Costa Rica. The remaining species are distributed in the following institutions: California Academy of Sciences (CAS) (4.8%), Scripps Oceanographic Institute (SIO) (5.2%), National Echinoderm Collection “Dr. Ma. Elena Caso” from the National Autonomous University of Mexico (ICML-UNAM) (12.7%), the National Museum of Natural History, Smithsonian Institute (USNM) (35.1%), and the Harvard Museum of Comparative Zoology (19.2%). There may be material from Costa Rica in the Natural History Museum of Denmark (NCD) and the Natural History Museum of Los Angeles (LACM), however, there was no access to such collections. There are 9.6% that do not appear in museums, but are reported in the literature. Based on this revision, the taxonomic list of echinoderms for Costa Rica is updated to 293 species, 152 genera, 75 families, 30 orders and 5 classes. The Pacific coast of Costa Rica has 153 species, followed by the Isla del Coco with 134 and the Caribbean coast with 65. Holothuria is the most diverse genus with 25 species. Rev. Biol. Trop. 65(Suppl. 1): S272-S287. Epub 2017 November 01.